STATUTORY ATTRIBUTES OF FEMALE DIRECTORS AND EARNINGS QUALITY IN INDONESIA - Yeasy Darmayanti (Jurnal Ilmiah Ekonomi Dan Bisnis, 2023)
All parties with an interest in the company need quality earnings information for economic decision making. This creates a moral hazard on the part of management to use various means in order to provide good news for these parties. This study aims to examine the effect of various attributes required by law (namely business education background, proportion, years of service, and foreign citizenship) related to the presence of women in top management on the earnings quality of companies in Indonesia. With the sample criteria set, 467 observations were obtained for companies listed on the IDX in 2015 - 2018. The results obtained indicate that the business education background and foreign citizenship of female directors affect earnings quality. Meanwhile, the proportion and tenure of female directors have no effect on earnings quality.